AL-FANA DAN AL-BAQA, AL-ITTIHAD DAN AL-HULUL - Sitika, Achmad Junaedi; Rahmah, Elda Fadlia; Sumiyati, Lilis; Ilyas, Dwi Intan Febriyanti; Haq, Jamilah Qiyaafatul; Qolby, Hafshoh Robi’a (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Being as close as possible to Allah SWT is the goal of a Sufi's life. To reach that direction, a Sufi must take a long path that contains stations or maqamat. Among the maqomat are called fana and baqa.Sufism is a form of pure science that belongs to Islam. Morals and Sufism have a very close relationship. Before practicing Sufism, one must have morals so that it can be said that At tashawwufu nihayatul akhlaq while al-akhlaqu bidayatut tashawwuf. In Sufism, a suprarational approach is used, namely by intuition/wijdan, and Sufism is usually more directed to the inner form than the outer form, but it is not denied that there is also an outer form in it. Whatever the definition of tasawwuf, a Sufi, and then what relates to fana and baqa is all about showing that we do not exist without Him, and one of the forms of showing that is calling themselves nothing but His Essence. And that is the whole form of glorification of the kholik that is found at a certain level, perhaps the top level of glorification.Â